Characterization of software development companies in emerging economies - Gutiérrez-Diez, María del Carmen; López-Sisniega, Carlos Luis; Aguilar, Alma Lilia Sapién; Howlet, Laura Cristina Piñón (Archives of Business Research, 2017)
Software has become a ubiquitous element in modern societies and represents a high-value economic sector in the market. The objective of this work is to analyze its characterization, particularly in the region of Chihuahua, Mexico, by making a description and comparison of the situation of the companies oriented towards this sector, with respect to the cluster that already exists. T This characterization allows establishing a diagnosis of the sector, which will help to define strategies aimed at strengthening such companies, as well as establishing comparative elements for companies of the same sector in other latitudes. The main findings point out that the companies surveyed as well as the cluster share the same problem and can work on solutions together.